â€œPrionsâ€ â€“ A Basic Review - Skanda R2, Vanilarasu Thirumalai2, Ramakrishna Kamath2, Gayathri R1, Vishnu Priya V1* (Recent Research in Science and Technology, 2010)
Novel infectious particles, termed prions, composed of a single protein are causative agents of a group of diseases that produce lethal decline of motor function. Prion diseases are among the most intriguing illnesses. Prion diseases are fatal neurodegenerative disorders that can arise spontaneously, be inherited, or be acquired by infection in mammals. This article gives a basic over view of prion proteins and prion diseases.